Review of the South American whip scorpions (Thelyphonida: Arachnida) - Rowland, J. M. (Amazoniana, 2002)
The literature concerning South American thelyphonids presently supports recognition of about tecn Recent species of thelyphonids representing two genera. Comparative and diagnostic features deduced from this literature and from study of some of these species are provided herein together with a discussion of the relevant morphological characters. A general review of the biology.
Keywords: Thelyphonida